Low Fifth-Minute Apgar Score Analysed According to Robson Ten Group Classification at a Tertiary Hospital in Nigeria - Olakunle Makinde; Benjamin O. Awotundun; Nkencho Osegi (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: Robson classification can be used to analyze and audit other indices of delivery outcome besides cesarean section (CS). The objective is to analyze low fifth-minute APGAR scores according to Robson’s classification and present deducible conclusions.